The Importance of Using Visual in Delivering Information - Hidayah, Lintang Ruhil (VCD, 2023)
The difficulty of absorbing information without a visual form is a problem for some people regardless of age, but students experience this difficulty the most because of the daily learning process. The purpose of this study was to determine whether conveying information visually can support a person's learning process. The research method used is quantitative using questionnaires and literature studies from previous research as supporting data. The object of this research is male and female students, aged 17-24 years old. The results obtained are the use of visuals has a positive and significant effect on the delivery of information and can be a medium to support learning.